OPTIMASI MODEL TRANSPORTASI DALAM PENGUKURAN KINERJA MANAJEMEN RANTAI PASOKAN BERAS: STUDI KASUS DI PERUM BULOG DIVISI REGIONAL JAWA BARAT - Galuh Chandra Dewi; E. Gumbira-Sa’id; Idqan Fahmi (Jurnal Manajemen & Agribisnis, 2005)
The purpose of this study was to analyze the ability of West Java on providing the needs of rice through all over West Java as well as the surrounding regions; and to evaluate optimal rice distribution among the regions. It was predicted that the rice production volume in West Java and Banten Provinces tend to decrease, each for 3 806.33 Tons per quartile and 1 662.85 Tons per quartile. The optimal rice transportation network should be conducted through rice distribution from Cirebon Sub Regional Division to Ciamis Sub Regional Division or from Karawang Sub Regional Division to Cianjur Sub Regional Division. Rice distribution could be conducted from Cirebon, Indramayu, Karawang and Subang Sub Regional Divisions to Jakarta Raya Sub Regional Division